Effects of solid acid and base catalysts on pyrolysis of rice straw and wheat straw biomass for hydrocarbon production. (April 2022) - Ma, Yangyang; Li, Hongji; Yang, Huiqing; Zhu, Yaodi; Zhao, Lijun; Li, Miaoyun
Abstract: Surplus biomass is one of the most attractive feedstock as it is renewable and sustainable, which can be used for the production of biofuels/chemicals. However, biomass is contents higher oxygen, which is hindered in application as a fuel. For improving the bio-oil quality, a process parameter such as catalyst needs to be endured for production of fuel-grade bio-oil. Catalytic fast pyrolysis of rice straw (RS) and wheat straw (WS) were performed using basic (MgO and CaO) and acidic (ZSM-5 and Y-zeolite) catalyst at different reaction temperature. It was found the different compositions of feeds reacted differently with presence of different catalysts. Pyrolysis products were grouped as carbonyls, phenolics heterocyclic and aromatic hydrocarbons. Carbonyls were observed as major compounds under the non-catalytic condition. Higher amount of carbonyls (62.91%) was obtained at 400 °C in case RS, while in case of WS lower amount was found (57.72%) without use of catalysts. However, catalysts such as basic metal oxide are encouraged to formation of phenolics and ketones compound, while acidic catalysts were encouraged to formation of aromatic hydrocarbons. Moreover, higher amount of aromatic hydrocarbon (52.9%) was found with RS using Y-zeolite, whereas higher amount of phenolics (48.5%) was obtained with WS using CaO catalysts. Highlights: Acid and base catalytic pyrolysis of rice straw and wheat straw were studied. Acidic and basic properties of catalysts significantly influence the products. Higher aromatic hydrocarbon (52.9%) was found from rice straw using Y-zeolite. Higher phenolic (48.5%) was obtained with CaO catalysts with wheat straw.